2022
DOI: 10.3389/fped.2022.976060
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endovascular embolization for Vein of Galen malformations: An individual participant data meta-analysis

Abstract: IntroductionUnderstanding outcomes after Vein of Galen malformation (VOGM) embolization has been limited by small sample size in reported series and predominantly single center studies. To address these limitations, we perform an individual-participant meta-analysis (IPMA) to identify risk factors associated with all-cause mortality and clinical outcome after VOGM endovascular embolization.MethodsWe performed a systematic review and IPMA of VOGM endovascular outcomes according to PRISMA guidelines. Individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…This implies that embolization plays an important role in managing cerebral AVSs: however, beyond the good success rate of the procedure, the neurodevelopmental outcome can be affected by the size of the malformation and the systemic consequences of prolonged heart failure. Recently, Savage et al performed an individual-participant meta-analysis to identify risk factors associated with all-cause mortality and clinical outcome after VGAM endovascular embolization, including 307 subjects from different small samples ( 12 ). They found that a good clinical outcome was achieved in 68% of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that embolization plays an important role in managing cerebral AVSs: however, beyond the good success rate of the procedure, the neurodevelopmental outcome can be affected by the size of the malformation and the systemic consequences of prolonged heart failure. Recently, Savage et al performed an individual-participant meta-analysis to identify risk factors associated with all-cause mortality and clinical outcome after VGAM endovascular embolization, including 307 subjects from different small samples ( 12 ). They found that a good clinical outcome was achieved in 68% of them.…”
Section: Discussionmentioning
confidence: 99%
“…They found that a good clinical outcome was achieved in 68% of them. Furthermore, first embolization as a neonate [OR = 6.93; 95% CI (1.99–24.08)] and incomplete embolization [OR = 10.87; 95% CI (1.86–63.55)] were significantly associated with mortality, whereas first embolization as a neonate [OR = 3.24; 95% CI (1.47–7.15)], incomplete embolization [OR = 5.26; 95% CI (2.06–13.43)], and heart failure at presentation [OR = 3.10; 95% CI (1.03–9.33)] were also significantly associated with poor clinical outcomes ( 12 ). We confirm this trend: in our cohort, the infants who required more than an embolization had a poor outcome (P1 with a low score in fine and gross motor skills, P4 died, P5 had hydrocephalus and brain atrophy, P7 had focal seizures).…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no reliable tool for early prediction of clinical progress and prognosis in VGAM. Current best practice is to base therapy on the severity of heart failure without assessing further objective parameters [5, 16]. However, reliable early prediction of clinical progress would be of particular therapeutic importance, as interventional treatment in a decompensated state is associated with higher complication rates and higher mortality [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unsuitable for early postnatal assessment, as it relies on manifest organ dysfunction, which develops over time [5, 8, 14]. No other early, bedside marker is available to predict the severity of organ dysfunction, mortality, and short-term cerebral damage on magnetic resonance imaging (MRI) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Sequelae of prolonged venous hypertension during this period lead to permanent disability or death in ∼40% of patients. 2,3 Intervention in the neonatal stage also carries a significant risk of peri-procedural stroke and death. 4 Thus, safer and more efficacious VOGM therapies are urgently needed.…”
Section: Introductionmentioning
confidence: 99%